THE EFFECTIVENESS OF TEACHER’S CORRECTIVE FEEDBACK IN TEACHING WRITIN - Dini Yahdiyani (EEAL Journal (English Education and Applied Linguistics Journal), 2020)
The effect of Teacher’s Corrective Feedback in Teaching Writing is a strategy that effectively facilities in learning English. The students can be more aware with the errors that they made in their writing product and will not write the errors repeatedly. The method used in this study was pre-experimental design and it was conducted in one of Islamic High School in Garut class X IPA 1. Written test was given to every students of the class to find out students’ writing achievement before and after have been given treatments. Beside that the interview was conducted to gather more information about students’ responses toward the strategy. Based on the findings that the value of tobserve (17.372) > tcritical (2.0452) it can be define that tobserved was out of Ho area and it meant that Ha was accepted. Therefore, it was concluded that using teacher’s corrective feedback significantly affected students’ achievement in writing text.